Маяковский - Михайлов Александр Алексеевич (Жизнь замечательных людей, 1988)
Экземпляры: ф-1 (ретроконверсия) / Инвентарный номер: 23010 / Цена: 2.50 / Сис.шифр: 83.3(2Рос=Рус)6 / Авт.знак: М69 / ГРНТИ: 17.09 / ББК: 83.3(2Рос=Рус)6-8 Маяковский 4